2020
DOI: 10.1097/ccm.0000000000004380
|View full text |Cite
|
Sign up to set email alerts
|

Development of Persistent Respiratory Morbidity in Previously Healthy Children After Acute Respiratory Failure*

Abstract: Objectives: Acute respiratory failure is a common reason for admission to PICUs. Short- and long-term effects on pulmonary health in previously healthy children after acute respiratory failure requiring mechanical ventilation are unknown. The aim was to determine if clinical course or characteristics of mechanical ventilation predict persistent respiratory morbidity at follow-up. Design: Prospective cohort study with follow-up questionnaires at 6 and 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 29 publications
3
22
0
Order By: Relevance
“…22 Pulmonary dysfunction after survival might be or steroids. 14 Our study showed that 73.3% and 37.8% of our cohort needed assisted enteral feeding at PICU and hospital discharge, respectively.…”
Section: Discussionmentioning
confidence: 57%
“…22 Pulmonary dysfunction after survival might be or steroids. 14 Our study showed that 73.3% and 37.8% of our cohort needed assisted enteral feeding at PICU and hospital discharge, respectively.…”
Section: Discussionmentioning
confidence: 57%
“…We prospectively enrolled 250 previously healthy children from 0 to 24 months of age that required invasive ventilation for an index case of ARF secondary to respiratory illness at 10 participating pediatric intensive care units (PICUs) over 5 consecutive years. This multicenter cohort has been described in detail elsewhere ( Gandhi et al, 2020a ; Keim et al, 2020 ). Briefly, previously healthy children, who met at least one of the three criteria, 1) chest radiograph with either focal or diffuse infiltrative pulmonary process, 2) radiographic evidence of air trapping, or 3) clinical exam findings of lower respiratory tract illness, were determined to have primary respiratory cause of ARF.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown a significant decline in the functional status of pediatric ARF survivors at discharge ( Pollack et al, 2009 ). More specifically, persistent respiratory morbidity (PRM) occurred after 6 and 12 months of an ARF episode even in previously healthy children ( Keim et al, 2020 ). In addition, there is a considerable heterogeneity in the progression of the disease and long-term outcomes of pediatric ARF patients ( Keim et al, 2020 ), indicating a complex interaction between genetic and environmental factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the challenges to investigating mechanical ventilation in the pediatric population is that mortality is frequently used as a therapeutic endpoint, but the majority of deaths in pediatric patients on mechanical ventilation are due to neurologic causes rather than refractory hypoxemia ( Dowell et al, 2018 ). Up to 44% of children with no previous respiratory co-morbidities have long-term outcomes of pulmonary dysfunction after a pediatric intensive care unit (ICU) stay for acute respiratory failure including persistent need for adjunct therapies such as oxygen supplementation, bronchodilators, and corticosteroids, or persistent asthma or recurrent pneumonia ( Keim et al, 2020 ). These secondary markers of lung injury may therefore make for a useful alternative marker mortality ( Keim et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%